2007
DOI: 10.4049/jimmunol.178.2.976
|View full text |Cite
|
Sign up to set email alerts
|

CD27low CD4 T Lymphocytes That Accumulate in the Mouse Lungs during Mycobacterial Infection Differentiate from CD27high Precursors In Situ, Produce IFN-γ, and Protect the Host against Tuberculosis Infection

Abstract: The generation of effector, IFN-γ producing T lymphocytes and their accumulation at sites of infection are critical for host protection against various infectious diseases. The activation and differentiation of naive T lymphocytes into effector memory cells starts in lymphoid tissues, but it is not clear whether the Ag-experienced cells that leave lymph nodes (LN) are mature or if they undergo further changes in the periphery. We have previously shown that CD44highCD62Llow effector CD4 T lymphocytes generated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
43
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 52 publications
9
43
1
2
Order By: Relevance
“…CD27 downregulation seems to be part of a functional program rather than the result of interaction with CD70 (43). Memory CD4 ϩ T cells at tissue sites also display this phenotype (44). Its functional significance is presently difficult to envision, but it suggests a particular relevance of CD27/CD70 interactions for T cells at the tissue site, in line with data gathered from CD27 Ϫ/Ϫ mice (36).…”
Section: Discussionsupporting
confidence: 61%
“…CD27 downregulation seems to be part of a functional program rather than the result of interaction with CD70 (43). Memory CD4 ϩ T cells at tissue sites also display this phenotype (44). Its functional significance is presently difficult to envision, but it suggests a particular relevance of CD27/CD70 interactions for T cells at the tissue site, in line with data gathered from CD27 Ϫ/Ϫ mice (36).…”
Section: Discussionsupporting
confidence: 61%
“…CD27 À CD62L lo CD4 1 T cells have been reported to accumulate in lungs during murine MTB infection and secrete high levels of IFN-g [23]. In WT mice, bulk CD4 1 and CD8 1 T cells, as well as antigen-specific CD8 1 T cells, from lung down-regulated CD27 over the course of MTB infection ( Fig.…”
Section: Normal T-cell Development Without Slomentioning
confidence: 99%
“…CD27 is widely used as a marker of memory B cells in humans [22]. Studies in a TB mouse model and pulmonary TB patients have shown a reduced level of CD27 expression on antigenspecific CD41 T cells associated with the persistence of active TB, suggesting a high ratio of fully differentiated effector CD4 1 T cells and the presence of antigens in vivo [23,24]. Similarly, Figure 7.…”
mentioning
confidence: 99%